Juridical Analysis For Mediationland Dispute Resolution - Nanin Oktaviani; Habib Adjie (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
This study aims to find out whether the results of mediation can be accepted as a settlement step and what are the legal consequences of the results of this mediation. The research method used is empirical juridical, namely by comparing legal facts with the theoretical basis of law and applicable legislation. Based on the results of the research, the following results were obtained: 1) As a mediator function, based on Permenag Number 11 of 2016 concerning Settlement of Land Cases, ATR/BPN can resolve land ownership disputes through mediation, only for disputes that do not involve ministries, the results of mediation are taken from dispute resolution can be considered final and binding, and to have legal force, a peace deed is better madein front notary official and afterwards the deed is registered with the District Court; and 2) the legal consequences of the mediation results that have been registered with the District Court are the legal basis for the Head of the local ATR/BPN Office to change or repair the disputed land certificate as an effort to provide protection and legal certainty.